Individual Perspectives on the Wellness Recovery Action Plan (W.R.A.P.) as an Intervention in Mental Health Care - Horan , Linda (International Journal of Psychosocial Rehabilitation, 2016)
Objective: This study explored the experience of individuals with mental health difficulties who completed the Wellness Recovery Action Plan (W.R.A.P.) intervention. Participant perspectives on the therapeutic elements of the WRAP, its role in recovery and constructive feedback are presented. Methods: Using descriptive phenomenological methods, in-depth semi-structured interviews were conducted with four individuals with mental health difficulties who attended a WRAP programme in a community mental health centre in Ireland. Results: Overall, participants felt that completing the WRAP was a therapeutic group experience. The identification of early warning signs and crisis planning proved particularly valuable by individuals who felt more empowered to actively manage their own mental health. Qualitative perspectives from this study point to the importance of introducing the WRAP early in an individual’s recovery journey, and providing multiple opportunities to repeat and review the process. Conclusions and Implications for Practice: Results support the findings of earlier studies in which the WRAP was found to be a self-management programme that contributes to the recovery of individuals with mental health difficulties. Group peer support was valued by participants, but future research should study the effectiveness of the WRAP in comparison to other peer support programmes.